Controlled Release of Ampicillin by Surface Modified MCM-48 Molecular Sieves - Kumar Nath, Bipul; Nath Ganguli, Jatindra (Asian Journal of Chemistry, 2013)
The mesoporous MCM-48 molecular sieves was prepared by hydrothermal process and the outside surface of the catalyst was modified with hexamethyldisilazine. Ampicillin is a b-lactam antibiotic drug that has been used extensively to treat bacterial infections since 1961. The drug was doped inside the pores of surface modified catalyst and the drug release was studied from the matrix into a simulated body fluid. The materials were characterized by XRD, FT-IR, SEM and TGA. The drug adsorbed benign MCM-48 may be used for effective drug delivery.